Narratives that shape the professional identities of mathematics teachers - Felix, Clyde Benedict Aurelius (Rhodes University, Faculty of Education, Department of Education, 2014)
The central position in this study is that the professional identities, and consequently the classroom practices, of mathematics teachers are continuously being shaped by their narratives of past and present experiences. The primary research question explores the narratives that shape the professional identities of seven mathematics teachers; and the secondary research question, how their narratives shape their professional identities. Furthermore, the potential implications of this study for the design and implementation of pre-service teacher education programmes and in-service teacher development initiatives are considered. This study is framed by Socioculturalism; a theoretical perspective of human thinking as social in origin and of learning as participation in social practices. Futhermore, in line with Situated Learning Theory, the key theoretical notions are: identity (or learning as becoming); community (or learning as belonging); practice (or learning as doing); and meaning (or learning as experience). Identity is construed here as a conceptual bridge between learning and its cultural settings; and also between the individual and the social. In this study, the identity-shaping narratives of seven mathematics teachers, all purposively sampled from schools in the Port Elizabeth and Grahamstown education districts of the Eastern Cape Province of South Africa, were accessed via a narrative inquiry; followed by a horizontal analysis to identify common patterns or recurring themes in the narratives of all seven participants; and, a vertical analysis of the narratives of four of the participants to determine how their narratives shape their professional identities. Recurring themes that emerged during the horizontal analysis include the influence of: family support; role models; changing work environments; continuous professional development; professional recognition; religion; and, micro-politics. The vertical analysis demonstrated how, through a process of interpreting the narratives and restorying them into a meaningful core narrative; it is possible to gain insights into how personal narratives shape a professional identity. This study highlights the importance of listening to the narratives of mathematics teachers; because their professional identities, and consequently their teaching practices, are continuously being shaped by their narratives. It is anticipated that this research will be of interest and benefit to researchers, policy-makers, and teachers; especially in the area of Mathematics Education, where both narrative inquiry as a research method and research into teachers' professional identities are relatively new.
Keywords: Mathematics teachers -- South Africa -- Port Elizabeth; Mathematics teachers -- South Africa -- Grahamstown; Mathematics teachers -- Professional relationships; Mathematics teachers -- Training of; Mathematics -- Study and teaching -- South Africa -- Eastern Cape; Education -- South Africa -- Eastern Cape